A decentralized proportional-integral sliding mode tracking controller for a 2 D.O.F robot arm - Kader Ibrahim, Babul Salam; Bakar, Saleha; Ahmad, Mohd. Noh; Osman, Johari H. S. (2005)
Trajectory tracking with high accuracy is a very challenging topic in direct drive robot control. This is due to the nonlinearities and input couplings present in the dynamics of the arm. This paper deals with the tracking control of a class of direct-drive robot manipulators. A robust Proportional-Integral (PI) sliding mode control law is derived so that the robot trajectory tracks a desired trajectory as closely as possible despite the highly non-linear and coupled dynamics. The controller is designed using the decentralized approaches. Application to a two degree of freedom direct drive robot arm is considered.